2006
DOI: 10.1080/09583150500335491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host egg viability on reproduction and development ofTrichogramma cacoeciaeandT. principium(Hymenoptera: Trichogrammatidae)

Abstract: A combination of a sterile insect technique, resulting in infertile eggs, and of an egg parasitoid, should provide better control of codling moth than either alone. Non-choice laboratory experiments were conducted with infertile and fertile codling moth eggs to evaluate the potential parasitism and reproduction of Trichogramma cacoeciae Marchal and T. principium Sug. et Sor. The tendency of T. cacoeciae females to attack infertile eggs was similar to that for fertile eggs, whereas T. principium showed a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…He added that hosts with no embryo, females may show no preference for accepting a host within different parts of the host egg. The present results are disagree with those of Makee (2006) who found that the tendency of T. cacoeciae females to attack infertile eggs was similar to that of fertile eggs, whereas T. principium showed a greater preference for infertile eggs than fertile eggs, and fertility status of the host did not affect the number of eggs that were parasitized.…”
Section: Influence Of Infertile Eggs On Some Biological Aspects Of Trichogramma Effect On Percentage Of Parasitized Host Eggscontrasting
confidence: 99%
See 1 more Smart Citation
“…He added that hosts with no embryo, females may show no preference for accepting a host within different parts of the host egg. The present results are disagree with those of Makee (2006) who found that the tendency of T. cacoeciae females to attack infertile eggs was similar to that of fertile eggs, whereas T. principium showed a greater preference for infertile eggs than fertile eggs, and fertility status of the host did not affect the number of eggs that were parasitized.…”
Section: Influence Of Infertile Eggs On Some Biological Aspects Of Trichogramma Effect On Percentage Of Parasitized Host Eggscontrasting
confidence: 99%
“…Olson 1998 stated that, some of the fresh host eggs presented to females may have not been fertilized which may have also affected parasitoid survival. The present results are in agreement with that of Makee (2006) who mentioned that fewer F 1 progeny emerged from infertile eggs when parasitized than from fertile eggs. The present results are close to those of AN Dahlan Gordon Gordh (1997 who stated that 20% of parasitized infertile eggs (< 12 h old) produced adult wasps but their number was significantly lower (P < 0.05) than those from fertile eggs.…”
Section: Effect On Percentage Of Emerged Progenysupporting
confidence: 94%
“…(2005) report that the number of adult parasitoids T. cryptophlebiae that emerged from parasitized sterile false codling moth eggs was affected by host cross when female codling moths were irradiated. Also, Makee (2006) observed for T. cacoeciae and T. principium that fewer F 1 progeny emerged from infertile eggs when parasitized than from fertile eggs.…”
Section: Discussionmentioning
confidence: 91%
“…Zhagn and Cossentine (1995) reported similar findings in a host preference study involving Trichogramma platneri Nagarkatti on viable and non‐viable codling moth and other Tortricidae moths. Makee (2006) working with T. cacoeciae and Trichogramma principium Sug. & Sor on codling moth found that T. cacoeciae had a similar tendency to parasitize both fertile and sterile eggs, whereas T. principium showed a greater preference for sterile eggs than fertile eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The parasitization of the host egg depends on its acceptance, which in turn depends on its species and age, as well as on the existence of previous parasitization (Benoit and Voegele 1979, Houseweart et al 1982, Pak and Oatman 1982. In turn, host-egg fertilization seems to have no influence on parasitoid development and emergence (Makeea 2006).…”
Section: Introductionmentioning
confidence: 99%